REVIEW OF THE ARTICLE “AUGUSTO COMTE AND ÉMILE DURKHEIM: A ‘EASY SOCIOLOGY’”. - Moreira, Jhoanna D’Arc Araújo; Oliveira, Anderson de; Carmo, Cristiano Soares do (Revista Coleta Científica, 2021)
This is a review of the article entitled “Augusto Comte and Émile Durkheim: a “appeasing” sociology”. This article is by: Luís Augusto de Mola Guisard and Irineu Francisco Barreto Junior. The article reviewed here was published in the journal “Revista FMU Direito”. Ano 25, n.35, p.64-72, 2011. ISSN: 2316-1515.